2020
DOI: 10.1016/j.bja.2019.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reversal of deep neuromuscular block with sugammadex or moderate block by neostigmine on shoulder pain in elderly patients undergoing robotic prostatectomy

Abstract: Background: For some laparoscopic procedures, deep neuromuscular block has been shown to facilitate lower insufflation pressures and lower patient pain scores, and enhance postoperative recovery. We investigated the impact of deep neuromuscular block and its reversal on postoperative shoulder pain and outcomes after robotic prostate surgery. Methods: Elderly men undergoing robotic prostatectomy were randomised to deep neuromuscular block (target posttetanic twitch of 1e2 at the facial nerve) with sugammadex re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Previous studies concerning laparoscopic surgery under spinal anesthesia found that pneumoperitoneum gas induced shoulder pain even during surgery 24 . Our results showed that prolonged CO 2 inflation time was associated with the higher incidence of PLSP, consistent with previous research in robotic surgery 25 . Female patients’ height may contribute to higher CO 2 inflation volume in laparoscopic surgery 26 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies concerning laparoscopic surgery under spinal anesthesia found that pneumoperitoneum gas induced shoulder pain even during surgery 24 . Our results showed that prolonged CO 2 inflation time was associated with the higher incidence of PLSP, consistent with previous research in robotic surgery 25 . Female patients’ height may contribute to higher CO 2 inflation volume in laparoscopic surgery 26 .…”
Section: Discussionsupporting
confidence: 92%
“…A lower intra‐abdominal pressure is the most likely mechanism for improved recovery associated with the deep NMB approach. Our study did not find any difference in intra‐abdominal pressure which is consistent with other literature . Our study is the largest randomised trial investigating the deep NMB technique and, importantly, was conducted in a pragmatic manner where we did not control insufflation pressure.…”
Section: Discussionsupporting
confidence: 91%
“…The most common recovery outcomes assessed include postoperative pain and nausea, analgesia consumption, sedation and length of stay. Several studies showed no difference , where others primarily showed reduced abdominal or shoulder tip pain . This literature is confounded by a wide range of intra‐abdominal pressures and, therefore, difficult to associate the likely mechanism of benefit with the measured outcome.…”
Section: Introductionmentioning
confidence: 99%
“… 28 , 29 , 30 , 31 , 32 , 33 In addition, 10 studies were identified that used an inhalation agent. 14 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 Seven out of these 10 studies reported a benefit of deep neuromuscular block during inhalation anaesthesia on surgical working conditions. 14 , 15 , 16 , 17 , 18 , 20 , 21 …”
Section: Resultsmentioning
confidence: 99%
“… Comparator to deep NMB Hypnotic agent Depth of anaesthesia: BIS/MAC/vol.% Low pressure pneumoperitoneum? Inhalation anaesthesia Blobner and colleagues 14 Yes No NMB Desflurane BIS 40–50 No Dubois and colleagues 15 Yes Single Shot Desflurane MAC 1.0 No Fuchs-Buder and colleagues 16 Yes Moderate Desflurane 4.0–6.0% No Kim and colleagues 17 Yes∗ Moderate Desflurane 4.0–7.0% Yes Koo and colleagues 18 Yes∗ Moderate Desflurane BIS 40–60 Yes Ozdemir-van Brunschot and colleagues 20 Yes Moderate Sevoflurane MAC 1.0 Yes Yoo and colleagues 21 Yes∗ Moderate Sevoflurane BIS 40–60 Yes Veelo and colleagues 22 No On Demand Sevoflurane MAC 1.0 No Williams and colleagues 23 No∗ Moderate Unknown Unknown No Kim and colleagues 24 No∗ Moderate Desflurane 4.0–8.0% No Total intravenous anaesthesia Koo and colleagues 25 Yes∗ Moderate Propofol …”
Section: Resultsmentioning
confidence: 99%